2016
DOI: 10.1177/0954410016670418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of volute’s asymmetry on the performance of a turbocharger centrifugal compressor

Abstract: The effects of the volute's asymmetry on the performance of a turbocharger centrifugal compressor were studied using steady simulations and theoretical analysis. According to the steady simulation results, it is found that the volute's asymmetry has significant influence on the performance of the centrifugal compressor. The variation of the stage efficiency due to volute's asymmetry is up to 4%. Meanwhile, the volute's asymmetry restricts the compressor stable flow range by imposing a distorted outlet pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Another work focused on the influence of the distortion amplitude, which showed that the higher the amplitude of the volute-induced distortion, the narrower the stable flow range. 20 The work of Zheng et al 21 provided theoretical evidence that proves the relationship between flow field distortion and compressor flow stability; a theoretical model taking the flow field distortion into account was established to explain the flow instability behavior of compressors, and it was noted that the flow field distortion caused flow instability at certain flow passages in advance, hence triggering the whole compressor to stall or surge at a higher mass flow rate, narrowing the stable flow range and exacerbating the compressor flow stability. Additionally, non-axisymmetric flow control methods, such as the non-axisymmetric casing treatment, 22, 23 were reported to be able to adapt the flow field distortion and extend the stable flow range, which also proves the belief that flow distortion is harmful to flow stability, to some extent.…”
Section: Volute-induced Distortion and Volute Designmentioning
confidence: 99%
“…Another work focused on the influence of the distortion amplitude, which showed that the higher the amplitude of the volute-induced distortion, the narrower the stable flow range. 20 The work of Zheng et al 21 provided theoretical evidence that proves the relationship between flow field distortion and compressor flow stability; a theoretical model taking the flow field distortion into account was established to explain the flow instability behavior of compressors, and it was noted that the flow field distortion caused flow instability at certain flow passages in advance, hence triggering the whole compressor to stall or surge at a higher mass flow rate, narrowing the stable flow range and exacerbating the compressor flow stability. Additionally, non-axisymmetric flow control methods, such as the non-axisymmetric casing treatment, 22, 23 were reported to be able to adapt the flow field distortion and extend the stable flow range, which also proves the belief that flow distortion is harmful to flow stability, to some extent.…”
Section: Volute-induced Distortion and Volute Designmentioning
confidence: 99%
“…1821 Stall inception can occur first in the impeller inlet of the passage with the highest reverse pressure gradient. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Stall inception can occur first in the impeller inlet of the passage with the highest reverse pressure gradient. 22,23 The compressor stall usually occurs in the tip separation flow region, which is related to the casing wall static pressure distribution (CWSP). Therefore, many experimental and calculation studies on the CWSP of centrifugal compressors, such as Tamaki et al, 24 Harley et al, 25 and Yang et al, 26 have been conducted in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…As an asymmetric geometry component, the volute leads to the formation of a circumferentially non-uniform flow field in the compressor and seriously affects the performance and stability of the compressor. [6][7][8] Recently, increasing researchers have focused on the influence of the downstream static pressure distortion induced by the volute on the centrifugal compressor stall. In fact, the volute is a type of gas collecting and guiding device.…”
Section: Introductionmentioning
confidence: 99%